2010
DOI: 10.3113/fai.2010.0473
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Clinical Pilot Trial in a Single Cohort Group of rhPDGF in Foot Arthrodeses

Abstract: These results indicate that rhPDGF is a safe product and provides clinical/radiographic outcomes that justify the pursuit of randomized controlled studies comparing rhPDGF/TCP to autograft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 16 publications
1
42
0
Order By: Relevance
“…It is also noteworthy that the B2A-granule group in the current pilot study had a higher rate of complete union at 9 months 17 (greater than 67% bridging bone in the joint) compared to the autograft group (92% vs 75%), and compared to those rates cited in other studies (C. W. DiGiovanni et al, unpublished data, 2011). 7 This study showed a trend for autograft fusions to have less fusion mass compared to the B2A group, notably when the percentage fusion at 6 months was less than 67%. All of these observations suggest a more robust fusion with B2A-granule group, accepting that this study is underpowered to confirm this observation.…”
Section: Discussionmentioning
confidence: 91%
“…It is also noteworthy that the B2A-granule group in the current pilot study had a higher rate of complete union at 9 months 17 (greater than 67% bridging bone in the joint) compared to the autograft group (92% vs 75%), and compared to those rates cited in other studies (C. W. DiGiovanni et al, unpublished data, 2011). 7 This study showed a trend for autograft fusions to have less fusion mass compared to the B2A group, notably when the percentage fusion at 6 months was less than 67%. All of these observations suggest a more robust fusion with B2A-granule group, accepting that this study is underpowered to confirm this observation.…”
Section: Discussionmentioning
confidence: 91%
“…39 The authors concluded that this product was safe and it may be pursued further as an ICBG alternative, although few studies exist showing its effect in the foot and ankle. 39 Conclusions Autologous, allogenic, and synthetic graft materials have been used in ankle and hindfoot arthrodesis with varying degrees of success. Nonunion continues to be the most common reason for failure of foot and ankle fusion.…”
Section: Platelet-derived Growth Factormentioning
confidence: 97%
“…39 None of these patients had adverse events, and at 12 to 16 weeks, 44 of 59 (75%) patients showed moderate or complete osseous bridging. 39 The authors concluded that this product was safe and it may be pursued further as an ICBG alternative, although few studies exist showing its effect in the foot and ankle. 39 Conclusions Autologous, allogenic, and synthetic graft materials have been used in ankle and hindfoot arthrodesis with varying degrees of success.…”
Section: Platelet-derived Growth Factormentioning
confidence: 97%
“…This may be due to the logistics of applying these new techniques in the clinical setting, but also as they have not conclusively demonstrated clinical superiority over autologous bone grafts (18,29,30). …”
Section: Introductionmentioning
confidence: 99%